Binary Shufﬂed Frog Leaping Algorithm for Optimal Allocation of Power Quality Monitors in Unbalanced Distribution System - Mohammadi, Ashkan Doust; Mohammadi, Mohammad (Journal of Automation, Mobile Robotics and Intelligent Systems, 2024)
This paper deals with optimal detection of number and best locations of power quality monitors (PQMs) in an unbalanced distribution network based on the monitor reach area concept. The proposed model uses binary strings which represent the state presence or absence of PQMs in each buses of network. In this paper the binary version of shufﬂed frog-leaping algorithm (BSFLA) because of having ability to improve the search capability with a fast convergence rate is utilized for optimization process. The overall cost function is formulated to optimize the two indices which are monitor overlapping index and sag severity index. The only optimization constraint in this problem is that, the number of monitors that can detect voltage sags due to a fault at a specific bus must not be zero. In this study, DIGSILENT software is utilized for fault analysis while the optimization problem is handled by the BSFLA. To verify the proposed algorithm, the IEEE 34 Bus unbalanced distribution network, is considered as case studies and results are compared to the similar investigations so as to illustrate the effectiveness of proposed algorithm.